PRINCIPLES OF THE SYSTEM OF ECONOMIC SECURITY OF INDUSTRIAL ENTERPRISES UNDER THE CONDITIONS OF COMPETITION - TULCHYNSKA, Svitlana; TKACHENKO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article substantiates the principles of the system of economic security of industrial enterprises in conditions of competition. Ensuring the effective functioning of the economic security system of an industrial enterprise is a task for its competitiveness, stability and preservation of successful functioning on the market. Implementation of the system of economic security of an industrial enterprise involves the use of principles that trigger its functioning. These principles establish the basic rules and conditions that help achieve the set goals of economic security. They are focused on: ensuring financial stability, stability, technical independence, high competitiveness, improving personnel qualifications, minimizing the negative impact on the environment and protecting various aspects of the industrial enterprise. It is substantiated that a comprehensive approach to the creation of an economic security system can vary depending on the characteristics of an industrial enterprise, industry, market conditions and other factors, and the general principles include: complexity and systematicity, preventiveness, balance, flexibility and adaptability, interconnection and experience. The specified principles of economic security management are based on the following provisions, which contribute to the effective management of the economic security of the enterprise and ensure its stability and successful operation in a dynamic business environment, and take into account: industrial enterprises must conduct a systematic analysis of risks that may affect its economic security; the enterprise should consider the possibilities of diversifying its activities and resources; effective financial management is a key aspect of functioning in economic security; the enterprise must have financial reserves to cover unforeseen events or negative changes in market conditions; an industrial enterprise must be ready for changes and innovations occurring in the economic environment; managing the economic security of an industrial enterprise requires cooperation and interaction with all interested parties, such as customers, suppliers, partners, government bodies, etc. The correct application of the principles of the economic security system contributes to the formation of a reliable and effective system that ensures the sustainable development of the enterprise.
Keywords: economic security; system of economic security; management of the system of economic security; principles; competition; competitive conditions; industrial enterprise